PERBANDINGAN KINERJA PORTOFOLIO SAHAM WINNER - LOSER BERDASARKAN STRATEGI INVESTASI MOMENTUM - Sasmikadewi, Anak Agung Istri Agung; Rusmala Dewi, Made (E-Jurnal Manajemen, 2017)
One of the way to invest in stocks is to compare the performance of a portfolio of stocks that are performing well (winner) and stocks that are performing poorly (loser) based on momentum investment strategy. This study aims to determine the performance of winner and loser stock portfolio as well as to determine the significance of differences in the performance of winner-loser portfolio formation period with the period of ownership in the finance sector companies listed on the Indonesia Stock Exchange period 2013 - 2015. The population in this study were as many as 89 stocks. The samples used were as many as 70 companies by using purposive sampling method. Data analysis technique used is the technique of analysis of two different test average (dependent t test). The analysis showed that the winner stock portfolio performance resulted in a lower performance compared to the performance of the resulting stock portfolio loser in the period subsequent ownership and there are no significant differences between the performance of winner-loser stock portfolio formation period with the period of ownership. This indicates that the momentum investment strategy can not be applied in the Indonesian capital market.
Keywords: finance sector, momentum investment strategy, portfolio performance comparison